The Transformation of “Teh Ong”: Turning a Traditional Drink with Various Flavor Variants into a Superior Product in Banjar Lantangidung, Sukawati - Ni Luh Putu Putri, Setianingsih; Sudiarta, I Wayan; Rustini, Ni Made; Pratiwi, , Ni Luh Putu Yumi Mega; Jelita, Ni Putu Ayu Bunga; Indra, I Kadek (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This community service program,